(untitled) (Advancements in Homeopathic Research, 2023)
Anaemia is a major public health problem in India as it is estimated that most of the non-pregnant women of reproductive age group are anaemic. It occurs when there is decreased level of haemoglobin in red blood cells. The primary cause of anaemia is iron deficiency. Iron deficiency anaemia (IDA) may be present with other systemic diseases. People with mild and moderate iron deficiency anaemia may not have any sign and symptom. But more severe iron deficiency anaemia may cause fatigue, tiredness, shortness of breath or chest pain. Although Homoeopathy gives importance to the individualisation of the patients, for remedy selection, still then, some medicines are prescribed based on disease diagnostic features. Such medicines are not well proved, so they are known as rare/lesser-known medicines. Of course, their role in the management of certain diseases cannot be ignored. This article aims at showing the effectiveness of some lesser-known medicines in the treatment of iron deficiency anaemia.